THE EFFECT OF COMPETENCY AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE THROUGH ORGANIZATIONAL COMMITMENT IN LAKARSANTRI DISTRICT, SURABAYA CITY: PENGARUH KOMPETENSI DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI MELALUI KOMITMEN ORGANISASI DI KECAMATAN LAKARSANTRI KOTA SURABAYA - Idha Rinata Soemartono; Dewie Tri Wijayati Wardoyo; Andre Dwijanto Witjaksono (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This study aims to analyze the influence of leadership style on employee performance in Lakarsantri District, Surabaya City through work motivation. In this quantitative approach research, the SPSS analysis method is used. The results of the study show that competence and work motivation have an effect on employee performance. Competence and work motivation also have an effect on organizational commitment. In addition, organizational commitment has an effect on employee performance. Thus, competence and work motivation have an effect on employee performance through organizational commitment in Lakarsantri District, Surabaya City